A study of the inclusion complex formed between cucurcubit[7]uril and 1-[4-(dimethylamino)phenyl]-ethanone. (1st August 2022) - Feng, Xian-Hao; Yu, Zhi-Chao; Zhang, Wei; Redshaw, Carl; Prior, Timothy J.; Meng, Tie-Hong; Li, Chun-Rong; Tao, Zhu; Xiao, Xin
Graphical abstract: Q[7] was added to a solution of 1-[4-(dimethylamino)phenyl]-ethanone and CdCl2 and CaCl2 in HCl solution.The mixture was heated until complete dissolution. Following slow evaporation of the volatiles from the solution over a period of about three days, block colorless crystals of complex 1 were obtained. We have studied the interaction of cucurbit[7]uril (Q[7]) with 1-[4-(dimethylamino)phenyl]-ethanone (DAPE) using a variety of techiniques including 1 H NMR spectroscopy, UV–vis adsorption and fluorescence spectroscopies, Isothermal titration calorimetry and single crystal X-ray diffraction. Results revealed the formation of a 1:1 complex, whilst the molecular structure of the species [(Q[7]@DAPE)Ca(H2 O)3 ]2 (CdCl4 )2 ·31(H2 O) is reported. Abstract: In the work, we have studied the interaction of cucurbit[7]uril (Q[7]) with 1-[4-(dimethylamino)phenyl]-ethanone (DAPE) using a variety of techiniques including 1 H NMR spectroscopy, UV–vis adsorption and fluorescence spectroscopies, Isothermal titration calorimetry and single crystal X-ray diffraction. Results revealed the formation of a 1:1 complex, whilst the molecular structure of the species [(Q[7]@DAPE)Ca(H2 O)3 ]2 (CdCl4 )2 ·31(H2 O) is reported.